2019
DOI: 10.1111/asj.13207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grazing cows in an intensive silvopastoral system with Leucaena leucocephala on Panela cheese properties: yield, composition, fatty acid profile and sensory acceptability

Abstract: Yield, chemical composition, fatty acid profile, and sensory acceptability of Panela cheese produced from cows grazing in an intensive silvopastoral system (ISS) with Leucaena leucocephala and Cynodon nlemfuensis were evaluated and compared with Panela cheese from cows grazing a monoculture system (MS) of C. nlemfuensis only. The experiment lasted for 9 weeks in a tropical area in Mexico using ten crossbred cows (30–90 days of milking) assigned homogenously as five cows in each experimental group. No significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…The results of the evaluation of odour and avour were similar to Moneeb et al (2019), who reported values of 6.1, 6.4, 6.3 and 6.6 for panela (fresh) cheese made with milk from cows under two feeding systems (monoculture and intensive silvopastoral systems); although these authors used a 9-point hedonic scale, where nine was 'I like it very much'; ve, 'I do not like nor dislike'; and one, 'I don't like it' to nd out its acceptability among the panellists.…”
Section: Sensory Assessment Fresh Cheesesupporting
confidence: 66%
“…The results of the evaluation of odour and avour were similar to Moneeb et al (2019), who reported values of 6.1, 6.4, 6.3 and 6.6 for panela (fresh) cheese made with milk from cows under two feeding systems (monoculture and intensive silvopastoral systems); although these authors used a 9-point hedonic scale, where nine was 'I like it very much'; ve, 'I do not like nor dislike'; and one, 'I don't like it' to nd out its acceptability among the panellists.…”
Section: Sensory Assessment Fresh Cheesesupporting
confidence: 66%
“…Moreover, the use of this type of system has the following benefits: increase soil fertility and conservation, improve thermal comfort of animals, possibility to increase the diversification of biodiversity and also, have a higher production and more quality in forage and animal production (SIERRA et al, 2002;POWER et al, 2003;YAMAMOTO et al, 2007;TUCKER et al, 2008). This system brings among many other benefits a better ambience for animal Brazilian Journal of Development, Curitiba, v.9, n.1, p. 1155-1178, jan., 2023 production, avoiding the mitigating effect of thermal stress in cattle leading to an improvement in productivity as well as milk quality in breeding systems that make use of this type of consortized dairy cow breeding in environments shaded by forestry (KINCHEL et al, 2014;MONEEB et al, 2019;DENIZ et al, 2019;LEITE DA SILVA et al, 2020).…”
Section: Introductionmentioning
confidence: 99%